TRADISI SONGGOT-SONGGOT ETNIS BATAK TOBA DI DESA TOMOK KECAMATAN SIMANINDO KABUPATEN SAMOSIR - Sinurat, Icha Inri Manuela; Rumapea, Murni Eva Marlina (Institut Agama Islam Ngawi, 2024)
Abstract: This study aims to describe the process of implementing the Batak Toba ethnic songgot tradition, describe the function of the Batak Toba ethnic songgot tradition and describe the community's view of the Batak Toba ethnic songgot tradition in Tomok Village, Simanindo District, Samosir Regency. The method used in research is qualitative research method with a descriptive approach. This research was conducted in Tomok Village, Simanindo District, Samosir Regency. Data collection techniques carried out are interviews and documentation. This study concluded that the songgot tradition is one of the traditions to get offspring, to afamily if it does not have children. The function of the songgot-soggot tradition is to Mangelek tondi (restore the soul) as well as pray to get what the heart desires. The people of Tomok Village still believe in the tradition of songgot-songgot, a culture that has been passed down.Keywords: Songgot-songgot Tradition, Batak Toba, Mangelek Tondi